HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN PEMBENTUKAN SIKAP POSITIF ANAK PADA IBU PENGURUS PKK DESA GIRIROTO TAHUN 2025 - Sandra Kristiani Barkah Kartikasari; Heru Sri Suryanti, Hera; Jawandi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the correlation between parenting styles and the formation of positive attitudes in children among PKK (Family Welfare Movement) administrators in Giriroto Village in 2025.This research was conducted in Giriroto Village, Ngemplak District, Boyolali Regency, Central Java. The sampling in this study consisted of PKK administrators in Giriroto Village who have at least adolescent-aged children. This study used a quantitative approach with a correlational design. The correlational research aimed to identify the relationship between parenting styles (independent variable) and changes in children’s positive attitudes (dependent variable).Based on the results of the study conducted on 20 PKK administrators in Giriroto Village, it can be concluded that there is a positive and significant relationship between parenting styles and the formation of children’s positive attitudes. The Pearson correlation test showed a correlation coefficient value of 0.690 with a significance value of 0.095. This coefficient indicates that the relationship between the two variables falls into a moderately strong and positive category, meaning that the better the parenting style applied to children, the greater the tendency for positive attitudes to be formed in children. Therefore, parenting styles play an important role in supporting the formation of positive attitudes in children.